Nursing Diagnosis Frequently Enforced by Nurse to Clients with Ischemic Stroke - Nita Arisanti Yulanda; Kharisma Aji Martadi; Anggelisa Larasati; Ikbal Fradianto (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims : This study is to find out the most diagnoses in stroke patients so that they can arrange appropriate interventions. Design: This study is a retrospective study using the descriptive anaysis. Methods :. The population of this study were all medical records of patients with stroke in 2018 - 2019 in Installation of Tanjungpura University Hospital. The study sample was selected using a purposive sampling method with inclusion criteria, namely patients with ischemic stroke, active patients undergoing outpatient care. The number of samples used was 100 medical record documents of stroke patients. The method of data collection is carried out by checklist instrument. Results : The results of the study were 6 nursing diagnoses that were often enforced by nurses in ischemic stroke patients, namely nursing diagnoses of . Impaired physical mobility ( 59 %), acute pain ( 24%), activity intolerance ( 7%), risk for ineffective cerebral tissue perfusion (5%), impaired verbal communication (3%) and impaired skin integrity (2%). However, of the 6 diagnoses, there were 2 nursing diagnoses written that were not in accordance with the labels on the 2015-2017 NANDA, however namely impaired skin integrity (100%) and impaired verbal communication (46%). Conclusions : It is recommended to increase the socialization of nursing diagnoses so that nurses write a diagnosis according to the diagnosis label used as a reference for writing documentation.